Calculations of environmental benefits from using geothermal energy must include the rebound effect. (March 2017) - Atlason, R.S.; Unnthorsson, R.
Abstract : Highlights: Savings of carbon emission from the Icelandic society have previously been over estimated. Previous studies have not included the rebound effect, or the change in consumption behavior because of cheap energy access. Savings in Iceland are likely to be between 164 and 361 million tons of CO2 equivalents between the years 1969 and 2014. Savings are similarly estimated to be between 76 and 142 million tons of CO2 equivalents between 1994 and 2014. This paper demonstrates how the rebound effect can be included in calculations of carbon emission savings. Abstract: When considering the environmental benefits from converting to renewable energy sources, the rebound effect is often omitted. In this study, the aim is to investigate greenhouse gas emission reduction inclusive of the rebound effect. We use Iceland as a case study where alternative consumption and energy production patterns are simulated using data from countries with similar environmental conditions but do not use geothermal or hydropower to the same extent as Iceland. Because of the rapid shift towards renewable energy and exclusion of external energy provision, the country is considered suitable for such a study. It was found that real emission reductions are most likely overestimated by previous calculations. Results show that between 1969 and 2014 greenhouse gas emission savings are likely to be between 164 and 361 million tonnes of CO2 equivalents. Between 1994 and 2014 savings are likely to be between the range of 76 and 142 million tonnes of CO2 equivalent. This study sheds a stronger light on the real observed environmental benefits when changes in consumption pattern are included in calculations stating greenhouse gas emission reductions.